Rain Fall: a Major Factor Leading to Outbreak of Teak (Tectona grandis) Defoliator, Hyblaea puera Cramer (Lepidoptera : Hyblaeidae) in Commercial Teak Plantation - Loganathan, J.; David, P. M. M. (Indian Forester, 1999)
Investigations carried out at three commercial Teak plantations in South India during January 1996-February 1997 revealed that outbreaks of defoliator H. puera occurred on Teak following early seasonal showers. Rainfall that had highly significant positive influence on defoliator incidence appeared to be the probable cause for defoliator outbreak. Delay in downpour lead to delay in defoliator infestation and vice-versa. However, rainfall appeared to have no effect in sustaining the epidemic infestation.